The Influence of Brand Image, Brand Trust and Service Quality on Brand Loyalty at Patra Malioboro Hotel - Mustofa; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The hotel industry is increasingly developing after the Covid-19 pandemic along with the development of tourism. This situation also has an impact on the level of competition in the business. This study was conducted at Patra Malioboro Hotel to analyze the significant impact of brand image, brand trust and service quality on brand loyalty. The sampling technique used purposive sampling with 100 domestic guests who used the services of The Patra Malioboro Hotel as the research sample. The data analysis tool uses Multiple Regression Analysis. Hypothesis testing proves that brand image, brand trust and service quality has a major impact on brand loyalty of The Patra Malioboro Hotel. Brand trust is the dominant factor influencing brand loyalty.